PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN (P2TP2) PROVINSI BALI (Sekilas Tentang Lembaga Perlindungan Perempuan) - Kebayantini, Ni Luh Nyoman (Jurnal Studi Jender SRIKANDI; Vol. 3, No. 2 Juli 2004, 2012)
Nowadays, the topics about gender still dominate the discussion on every meeting, seminar, workshop and other discussion, although the struggling to balance and to equivalence it done since 1978. It indicates that there are still unbalanced of gender especially for the women in our society. Those unbalanced can be seen in such kind of area like education, law, economic, health and employment. Besides, the hardness to women and children increase as seen at the increasing of women-children trading, sexual abusing or raping to women and children. To protect the women and children from the abuse, the government found an institution named The Centre of Woman Efficiency Integrated Service.
Keywords: Pusat Pelayanan Terpadu, Pemberdayaan Perempuan.